Rancang Bangun Aplikasi Manajemen Informasi Berita Berbasis Android - Maharsa Pradityatama (CV. Multi Kreasi Media, 2022)
Today's information media are increasingly important, information media can be a place for people to get information, exchange ideas and interact with each other. One of the information media is news, news is a quick report of an event or factual event. People need for the latest information is currently high, if an information is missed for a few hours, it is no longer updated. Accessing news that can be accessed anywhere and anytime with a smartphone is very helpful for someone who is busy, quick access is needed to view news information. Android operating system is an open source-based operating system that facilitates developers to develop various kinds of android applications. Making an Android-based news information management application using the Java programming language with MySQL database storage. So the final result of the research is the design of an Android-based news information management application that has several main feature menus, namely uploading news along with pictures or videos along with news information, reading detailed news information, viewing news with video.